Vocational High School Teachers' Beliefs on Teaching Speaking Skills in English as a Foreign Language - Khairunnisa, Khairunnisa; Sudana, Dadang; Rodliyah, Rojab Siti (Jurnal Penelitian Pendidikan, 2020)
Before improving and developing the best method for teaching speaking in vocational schools, teachers' beliefs and beliefs should be unpacked to know how far the understanding of them. This article presents a case study that examined vocational school teachers' beliefs and practices to do teach as a foreign language, especially speaking comprehension. Based on the case study, four teachers were asked to fill the questionnaire to get the information about their beliefs; forty students were confirming the practices of those beliefs in the classroom through questionnaires. Findings unfolded English teachers' views related to their roles, the students' positions, the effective English speaking teaching, the language used in the classroom, and the goals of teaching speaking. Based on the students' statement, the convergence of educators' beliefs to practices arrived at half of the teachers. The study results give teachers implications for constructing valid thoughts and provides an overview for stakeholders to decide an efficient teaching strategy.